Association between external and internal lymphedema and chronic dysphagia following head and neck cancer treatment. Issue 1 (1st October 2020) - Jeans, Claire; Ward, Elizabeth C.; Brown, Bena; Vertigan, Anne E.; Pigott, Amanda E.; Nixon, Jodie L.; Wratten, Chris; Boggess, May
Abstract: Background: To examine the relationship between chronic external and internal head and neck lymphedema (HNL) and swallowing function in patients following head and neck cancer (HNC) treatment. Methods: Seventy‐nine participants, 1‐3 years post treatment were assessed for external HNL using the MD Anderson Cancer Centre Lymphedema Rating Scale, and internal HNL using Patterson's Radiotherapy Edema Rating Scale. Swallowing was assessed via instrumental, clinical and patient‐reported outcome measures. Results: HNL presented as internal only (68%), combined external/internal (29%), and external only (1%). Laryngeal penetration/aspiration was confirmed in 20%. Stepwise multivariable regression models, that accounted for primary site, revealed that a higher severity of external HNL and internal HNL was associated with more severe penetration/aspiration ( P  < .004 and P = .006, respectively), diet modification ( P  < .001 both), and poorer patient‐reported outcomes ( P = .037 and P = .014, respectively). Conclusion: Increased swallowing issues can be expected in patients presenting with more severe external HNL and/or internal HNL following HNC treatment.